Consistent quantum theory - Griffiths, R. B. (Robert Budington) (Cambridge University Press, 2002)
Illustrating basic quantum principles using simple examples, Griffiths clarifies topics that students and their teachers often find confusing. A supplement to traditional texts, this book is accessible to graduate and advanced undergraduate students. It will also be of interest to physicists and philosophers working on the foundations of quantum mechanics.